Effects of dried distillers grains with solubles on sow carcass fat quality - Houser, Terry A.; Gipe, A.N.; Goehring, B.L.; Hillyard, S.L.; Duttlinger, A.W.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A pilot experiment was conducted to determine the effects of feeding nonpregnant (open) sows a diet containing 50% dried distillers grains with solubles (DDGS) on growth and carcass fat quality. A total of 8 open sows were allotted to 1 of 2 diets by parity and BW. One diet was a standard corn-soybean meal-based gestation diet; the second diet was a corn-soybean meal-based diet that contained 50% DDGS. All sows were fed 5 lb/d of feed in a single feeding for 92 d. All sows were harvested on d 92 at the Kansas State University Meat Laboratory for determination of carcass fat quality. As expected, no differences in BW or backfat change were found (P > 0.62) for the feeding period. Additionally, no differences (P > 0.23) in lipid oxidation as measured by 2-thiobarbituric acid reactive substances (TBARS) assay were reported either initially or after 5 d of retail display for sows fed 50% DDGS compared with controls. Lipid oxidation increased (P < 0.003) as measured by TBARS assay for both treatments from d 1 to 5 as expected. Jowl fatty acid analysis revealed an increase in linoleic acid (P < 0.01), total polyunsaturated fatty acids (P < 0.01), and the ratio of polyunsaturated fatty acids to saturated fatty acids (P < 0.03). Also, there was a trend for increased jowl iodine value (P < 0.08) for sows fed 50% DDGS compared with the controls. In summary, feeding 50% DDGS to open sows for 92 d did not significantly affect BW, backfat, and lipid oxidation compared with controls. However, feeding 50% DDGS increased the concentration of linoleic acid and total polyunsaturated fatty acids and tended to increase jowl iodine value compared with controls.
Keywords: Carcass fat quality; Dried distillers grains with solubles; Lipid oxidation; Sow